MASUKNYA 34 WARGA NEGARA ASING ASAL CHINA DITINJAU DARI PERMENKUMHAM NOMOR 27 TAHUN 2021 - Erry Daffa Ramadhan; Tri Sulistyowati (Reformasi Hukum Trisakti, 2023)
The Government of the Republic of Indonesia implemented the PPKM policy to limit Foreign Citizens to suppress the spread of COVID-19. In August 2021, 34 people originating from China entered Indonesian territory. The problem of this research is how did 34 foreign nationals from China violate PPKM restrictions against the provisions of PermenKumHam No. 27 of 2021 and what are the efforts made by the government in resolving the case of the entry of the 34 foreign nationals from China. This research is a juridical research that is analytical descriptive. Secondary data is data that is used with qualitative and deductive analysis as a method to draw a conclusion. The conclusion of this study is that the entry of 34 people originating from China entering Indonesian territory via Soekarno-Hatta International Airport does not violate the provisions in the Regulation of the Minister of Law and Human Rights Number 27 of 2021 which provides an exception for holders of Limited Stay Permits (ITAS). Completion efforts made by the government are to provide quarantine for 8 days and must show a complete vaccine dose certificate